Realistic agendas for future of e-government implementation in Malaysia - Abd Hamid, Siti Nur Illani; Romle, Abd Rahim; Mansor, Mohd Hafiz (AENSI Publisher, 2015)
In line with the development of functional diversity in providing services to the community, the government has applied the use of ICT in the public sector to improve the capacity and quality of public sector services.The phenomenon of e-government is not only able to change the way public sector service delivery, but also a similar change pattern in electronic government and the community.Through the services provided, the community can take full advantage of using e-government.Along with the development of electronic government, various attempts have been made to encourage people to use this application. Unfortunately, the number of Malaysians consumer use electronic government applications is still not achieving the optimum level of usage.Although efficient service innovation is seen, but the efficiency depends on its acceptance among people. Use of this innovation on a large scale is very important so that the electronic government policy objectives will be achieved.For that reason, this research seeks to determine the effectiveness of the application of egovernment at the local level in the Municipal Council Seberang Perai (MPSP), Penang, Malaysia. The study involved users of services to be provided electronically in MPSP. This research has been made by using mixed methods, quantitative and qualitative in studying the effectiveness of e-government implementation. From this study, the researchers aim that e-government system being used optimally by society and civil servants, but improvement is needed to rectify the effectiveness of this system in local government administration which is the Municipal Council Seberang Perai (MPSP).